Non-medical prescribing in palliative care: A regional survey. (February 2015) - Ziegler, Lucy; Bennett, Mike; Blenkinsopp, Alison; Coppock, Sally
Background: The United Kingdom is considered to be the world leader in nurse prescribing, no other country having the same extended non-medical prescribing rights. Arguably, this growth has outpaced research to evaluate the benefits, particularly in areas of clinical practice where patients have complex co-morbid conditions such as palliative care. This is the first study of non-medical prescribing in palliative care in almost a decade. Aim: To explore the current position of nurse prescribing in palliative care and establish the impact on practice of the 2012 legislative changes. Design: An online survey circulated during May and June 2013. Participants: Nurse members ( n  = 37) of a regional cancer network palliative care group (61% response rate). Results: While this survey found non-medical prescribers have embraced the 2012 legislative changes and prescribe a wide range of drugs for cancer pain, we also identified scope to improve the transition from qualified to active non-medical prescriber by reducing the time interval between the two. Conclusion: To maximise the economic and clinical benefit of non-medical prescribing, the delay between qualifying as a prescriber and becoming an active prescriber needs to be reduced. Nurses who may be considering training to be a non-medical prescriber may be encouraged by the provision of adequate study leave and support to cover clinical work. Further research should explore the patients' perspective of non-medical prescribing.